The potential impact of washing machines on laundry malodour generation. (22nd February 2013) - Stapleton, K.; Hill, K.; Day, K.; Perry, J.D.; Dean, J.R.
Abstract A multidisciplinary approach has been adopted to investigate and identify the source of malodour in washing machines and the potential for cross‐contamination of laundry. Four washing machines were olfactively graded, and the number of colony‐forming units (CFUs) bacteria was determined in four specific locations. Then, samples of terry‐towel and fleece were washed, without the use of detergent, in the machines, and the occurrence of malodour over a 52‐h period was assessed. Analysis of the scrapings from the four locations in the two malodorous machines identified a plethora of volatile organic compounds (VOCs) by either olfactory detection or mass spectral identification post‐gas chromatographic separation. In addition, microbiological analysis from the swabs from the four locations within all four washing machines was carried out. Quantitative analysis of VOCs from 66 microbiological isolates from either the washing machines or fabrics was carried out. In total, 10 VOCs were identified: dimethyl disulfide, 3‐methyl‐1‐butanol, 2, 4‐dithiapentane, dimethyl trisulfide, 2‐tridecanone, indole, 2‐phenylethanol, isovaleric acid, isobutyric acid and 1‐undecene.